1996
DOI: 10.1177/1358863x9600100102
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Intermittent Claudication: Relationship with Laboratory Exercise Performance

Abstract: In patients with peripheral arterial disease, limitation of exercise capacity will reduce the level of everyday physical activity and affect the quality of life. This study was designed (1) to examine the health-related quality of life of patients with intermittent claudication, and (2) to verify whether treadmill performance is related to the patient's perceived ability to function in the community. In 251 patients with intermittent claudication and 89 matched normal subjects, quality of life was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 18 publications
4
49
0
1
Order By: Relevance
“…13,14 Evidence for this recommendation includes poor correlation between physician and patient assessment of the impact of IC on the patient's QOL, 15 poor correlation between ABI and self-reported level of disability, 16 and poor correlation between objective measures, such as treadmill walking distance and QOL. 17 Similar to prior studies, discordance was observed between treadmill performance, free step activity, and QOL measures in the treatment arms of CLEVER. 10 The greater improvement in QOL in the stent arm may reflect the gratification of symptom relief, as 43% of the stent group were free of IC at 6 months, compared with 21% of the supervised exercise group.…”
supporting
confidence: 78%
“…13,14 Evidence for this recommendation includes poor correlation between physician and patient assessment of the impact of IC on the patient's QOL, 15 poor correlation between ABI and self-reported level of disability, 16 and poor correlation between objective measures, such as treadmill walking distance and QOL. 17 Similar to prior studies, discordance was observed between treadmill performance, free step activity, and QOL measures in the treatment arms of CLEVER. 10 The greater improvement in QOL in the stent arm may reflect the gratification of symptom relief, as 43% of the stent group were free of IC at 6 months, compared with 21% of the supervised exercise group.…”
supporting
confidence: 78%
“…Specifically, patients with PAD often describe a sense of shame and powerlessness; limitation in exercise tolerance; being a burden to family and friends; and depression and a diminished overall quality of life. [12][13][14][15][16] This study further explored this area and reveals results that are unique in several aspects. In contrast to other studies, which concentrated on individuals with symptomatic PAD, this study objectively measured the ABI and methodically ascertained PAD-related hospital discharge diagnoses and intermittent claudication in a large communitybased population to define PAD cases and noncases for comparison.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, treadmill MWD may not be correlated with the "true" free-living MWD at usual pace and on a flat surface 5 and does not correlate with the patient's perception of disability. 6 Various methods that do not require a treadmill have been proposed to estimate walking capacity, including "unguided" self-estimated MWD, estimation of walking impairment by standardized questionnaires, and the 6-minute walking test.…”
mentioning
confidence: 99%